ToxDP2 Database: Toxicity prediction of dietary polyphenols. (15th February 2022) - Sinha, Meetali; Sachan, Deepak Kumar; Bhattacharya, Roshni; Singh, Prakrity; Parthasarathi, Ramakrishnan
Graphical abstract: Highlights: Exposure to dietary polyphenols has increased across the globe. It is essential to understand potential risk of polyphenols consumption. ToxDP2 fulfills the toxicity data gaps in the domain of food safety. The database provides physicochemical, ADMET and various toxicological endpoints. Useful for the development of nutraceuticals and diet formulations. Abstract: Polyphenols are bioactive substances that minimize the risk of a variety of chronic diseases. Exposure to polyphenol bioactive compounds in our diet has increased across the globe, with amplified expectations from consumers, industry, and regulators centered on the potential benefits and essential safety of these compounds. Several data resources for beneficial properties of dietary polyphenols are present; however, toxicological information remains partial. We present a dynamic web-based database to assess dietary polyphenols' safety and fulfill the toxicity data gaps in the domain of food safety. The database (ToxDP2) comprises 415 dietary polyphenolic compounds, distributed into 15 subclasses with 25, 792 collected and predicted data points. This web server facilitates the exploration of polyphenols for divergent applications. The data-driven approach on the ToxDP2 provides researchers with an understanding of polyphenols structure–function-toxicity relationships beneficial for developing nutraceuticals, pharmaceuticals, herbal supplements, and formulations.